A Novel H∞ Robust Control Strategy for Voltage Source Inverter in Microgrid - Shi, Hongtao; zhang, Jie; Zhou, Jian; Li, Yifan; Jiang, Zhongnan (Frontiers in Energy Research, 2021)
The voltage control performance of the voltage source inverter (VSI) in the microgrid may change under different load conditions. However, in the case of traditional control strategies, the robustness of VSI is insufficient. In response to the above problems, a novel robust control scheme for VSI in microgrid based on H∞ hybrid sensitivity is proposed in this paper. The grid-side interference during the VSI operation is taken as the variable and the sensitivity function is designed to build H∞ robust voltage controller for VSI. In addition, an adaptive virtual impedance group is designed to further improve the voltage control robustness under a variety of operation conditions. Finally, comparative simulation experiments are carried out to verify the anti-interference ability of the proposed control strategy under different working conditions.